Development of Mie-Diabet as a Healthy Food Option For Millennials in Maros Regency Pentol.in - Maulana, Andi; Amirah, Sitti; Mirawati, Mirawati; As’ad, Nur Asyirah; Adimi, Nurhikma; Kamri, Andi Khaedhir (Abdimas Indonesian Journal, 2024)
Mie-Diabet is a culinary concept that emphasises the utilisation of balanced and nutritious ingredients to produce noodles that can improve health and quality of life. In contemporary society, a balanced and nutritious diet is essential for sustaining physical health, particularly for the younger population that favours inexpensive food options. Mie-Diabet enhances quality of life by supplying essential nourishment and mitigating the risk of sugar-related ailments. Mie-Diabet embodies the principle of nutritious cuisine that can be appreciated by individuals of all ages, serving as an accompaniment to various dishes, including meatballs, which are particularly favoured by the Indonesian populace. Pento.in is an UMKM in Maros Regency that has popularity among the young and is a favoured snack among the populace. Pento.in has been operational for nearly a year but has not yet obtained a PIRT permission. Consequently, the UMI professor team identifies a chance to present Mie-Diabet to the Maros community through partnership with Pento.in, while simultaneously promoting UMKMs to secure PIRT and Halal certification in the future. Furthermore, Mie-Diabet will assist in preserving physical condition by substituting high-sugar meals, such as other harmful instant noodles. The education delivered has demonstrated efficacy in enhancing the UMKM community's comprehension of the Mie-Diabet product. The substantial rise in average scores post-education clearly indicates that the observed difference is statistically significant and not attributable to chance. These instructional initiatives can significantly aid UMKMs in comprehending and integrating innovative items that enhance public health.